2005
DOI: 10.1002/pssc.200460190
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium centres in alkaline‐earth fluoride crystals

Abstract: Strong absorption in the vacuum ultraviolet region near the exciton edge was observed in Cd doped CaF 2, SrF2 and BaF2 crystals. The Cd ++ absorption band at 8.6 eV was observed in low doped BaF2 crystals. In SrF2 and CaF 2 the maximum of Cd ++ band cannot be resolved due to stronger overlapping with exciton bands. The calculations of geometry of Cd ++ and Cd + centres and Cd-related electron transitions were done using ab − initio Hartree-Fock and density functional methods. The experimental and calculated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…2). The shift was ascribed to be from strong absorption band [6]. In doped crystals we observe a strong relative decrease of excitation intensity above 10 eV against the excitation intensity in undoped crystals (see Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…2). The shift was ascribed to be from strong absorption band [6]. In doped crystals we observe a strong relative decrease of excitation intensity above 10 eV against the excitation intensity in undoped crystals (see Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Impurities , , have filled outer shells and have no own absorption bands with energies below 12 eV. However, new strong absorption bands appear very near to the exciton absorption edge in vacuum ultraviolet region [6]. Cadmium introduced impurity states lower the bottom of conduction band states and the transitions from surrounding fluorines to cadmium lead to the appearance of strong absorption just below the exciton edge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found a shift of the excitation edge for exciton emission to higher energies due to the strong Cd-related absorption in CaF 2 , SrF 2 , BaF 2 (for the example of BaF 2 see figure 3). Calculations show that the transitions from the valence band to Cd states should be 1-2 eV less than inter-band transitions [4]. Therefore, it was concluded that the Cd 2+ bands are due to the transitions from the top of valence band, arising from the fluorine states, to the Cd 5s states [4].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any emission of Cd 2+ centres in BaF 2 crystals. Therefore, the positions of the main absorption bands were taken from the respective absorption spectra have a strong band at 8.6 eV [4]. From the comparison of excitation spectra of undoped and Cd-doped BaF 2 crystals (figure 3) one can conclude that the dip at 9.7 eV is due to the second Cd 2+ absorption band.…”
Section: Excitation Spectramentioning
confidence: 99%
See 1 more Smart Citation